Online Training: an Alternative Solution of the Empowerment for Parents of Children with Autism - Herlina, Herlina; Susilana, Rudi (Journal of Education Technology, 2021)
This study aims at proving that Independent Intervention Program (Program Intervensi Mandiri or PIM) Online Training is an effective way to empower parents in handling children with autism. The research was performed through field experiment involving 11 parents of children with autism from a number of city in Indonesia. Subjects were given the PIM Online Training by platforms such as Zoom and WhatsApp. Training effectiveness data were seen from subjects’ self-evaluation result, prior and following the training. The result shows that after having the PIM Online Training, parents see themselves better in understanding the concepts about Autism Spectrum Disorder (ASD), social skills, intervention, and individual intervention program, and in the skill of designing the intervention program for their children with autism, compared to the condition prior receiving the training. Based on the result, the PIM Online Training is expected to be a proper solution to empower parents in designing social skill intervention program for their children with autism, without time, place, and cost limits.